The Spectrographic Analysis of Stutterer's Speech under Delayed Auditory Feedback - Ramesh CV (Journal of All India Institute of Speech and Hearing, 1970)
The development and influence of cybernetics has given rise to  a number of hypothetical  models, such as those by Fairbanks (1954) and Mysak (1966) which  describe the essential monitoring system for speech as closed feedback loops and have concluded that any disruptions in the monitoring system might  lead  to  speech disturbances.